The failure of universal theories of tort law - Goudkamp, J; Murphy, J (Cambridge University Press, 2016)
Many scholars have offered theories that purport to explain the whole of the law of torts. At least some of these theories do not seem to be specific to a single jurisdiction. Several appear to endeavor to account for tort law in at least the major common law jurisdictions or even throughout the common law world. These include Ernest Weinrib's corrective justice theory, Robert Stevens's rights theory, and Richard Posner's economic theory. This article begins by explaining why it is appropriate to understand these three theories as universal theories of tort law and why it is important that they be so understood. This explanation draws upon various overt claims (or other strong intimations) made by the theorists themselves to the effect that this is how their respective accounts should be understood. The article then proceeds to test these theories, all of which are leading accounts of tort law, against the evidence in Australia, Canada, the United Kingdom, and the United States. The parts of tort law on which we focus are (1) the breach element of the action in negligence, (2) the law that determines when a duty of care will be owed in respect of pure economic loss, (3) the law that governs the availability of punitive damages, (4) the defense of illegality, and (5) the rule in Rylands v. Fletcher and its descendants. The article concludes that none of the theories is a satisfactory universal account of tort law. All of them suffer from significant problems of fit in that they cannot accommodate (often even approximately) the areas of law that we discuss. Although each of the theories contains a great many valuable insights, they all nonetheless fall well short of accomplishing that which they are held out as providing. In the course of this analysis, the article explains why this is an appropriate line of criticism and identifies the degree of lack of fit that we regard as being “significant.”